2017
DOI: 10.1080/09168451.2016.1270742
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion and oxidative stability of O/W emulsions and oxidation of microencapsulated oil

Abstract: Oil-in-water (O/W) emulsions are among the dispersion systems commonly used in food, and these emulsions are in thermodynamically unstable or metastable states. In this paper, various methods for preparing O/W emulsions are outlined. Since the commodity value of food is impaired by the destabilization of O/W emulsions, experimental and theoretical approaches to assess the stability of O/W emulsions are overviewed, and factors affecting the dispersion stability of emulsions are discussed based on the DLVO theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 71 publications
1
4
0
1
Order By: Relevance
“…This observation can be explained considering that higher amounts of proteins better stabilize O/W emulsions. This observation has already been reported for other emulsions (Bai & McClements, 2016;Evans, Ratcliffe, & Williams, 2013;Miyagawa & Adachi, 2017). Fig.…”
Section: Stability Of the Emulsionssupporting
confidence: 86%
See 1 more Smart Citation
“…This observation can be explained considering that higher amounts of proteins better stabilize O/W emulsions. This observation has already been reported for other emulsions (Bai & McClements, 2016;Evans, Ratcliffe, & Williams, 2013;Miyagawa & Adachi, 2017). Fig.…”
Section: Stability Of the Emulsionssupporting
confidence: 86%
“…1), they expose a larger surface to the air, thus being more prompt to oxidation. In this regard, Miyagawa and Adachi (2017) showed demonstrated that a reduction of the oil droplet size suppresses or retards autoxidation. Microencapsulated lipids or oils exhibit distinct features in the oxidation process.…”
Section: Stability Of the Emulsionsmentioning
confidence: 99%
“…However, because many factors are related to the oxidation of lipids in the emulsions, the effect of oil droplet size is not simply assessed. Some contradictory results have been reported . It is reported that oil oxidation was more retarded to a greater extent in O/W emulsions with the smaller oil droplets .…”
Section: Introductionmentioning
confidence: 96%
“…Margarine is an emulsion of water droplets in oil (W/O) [1] and used as a low-fat alternative for butter and other fat-soluble spreads [2]. Whereas oil in water emulsions (O/W) have been investigated comprehensively [3][4][5][6][7], W/O emulsions have been studied scarcely and the characterization of their long-term stabilization still remains a challenging task in food science, limiting their potential application in the food industry. It is essential to understand the factors that affect the stability of an emulsion to develop high-quality emulsion-based food products, such as spreads, sauces and margarine [8].…”
Section: Introductionmentioning
confidence: 99%